Ambient Experience in Restitutive Treatment of Aphasia - McClung, Jill S.; Gonzalez Rothi, Leslie J.; Nadeau, Stephen E. (Frontiers in Human Neuroscience, 2010)
One of the greatest challenges to language rehabilitation is reconciling the fact that the same therapeutic intervention, provided to different individuals with similar types of stroke-induced aphasia, may result in divergent outcomes. In this paper, the authors reviewed existing literature to identify relevant ambient factors – those outside the control of the clinician – that may potentially influence functional language recovery in aphasia and response to treatment. The goal was to develop a clinical history-taking tool to assist clinicians in gathering information germane to each individual’s unique circumstances and environment, elements that may have previously been underestimated, to provide a complete inventory of potentially potent prognostic factors. First, two of the authors, speech-language pathologists experienced in aphasia rehabilitation, identified and categorized factors that seemed likely to influence aphasia outcomes. Then, a wide range of literature was reviewed in an effort to identify factors empirically found to be potent influences on aphasia recovery. Where studies relating these factors to aphasia were not found, relevant research from allied fields that examined recovery from brain injury is reported. Moreover, some factors thought to be potentially potent have yet to be examined. Finally, the ambient factors supported by evidence were categorized as facilitators or barriers to functional improvement, and the Ambient Influences on Outcome Checklist (AOC) was developed, including only those factors shown to be potent in the recovery process. It is hoped that this checklist can be used to more broadly assess potential prognostic influences in aphasia restitution, as well as spawn further research.